Technology Roadmap: Lab-on-a-Chip - Daim, Tugrul U; Suntharasaj, Pattharaporn (Revista de Administração da UFSM, 2010)
With the integration of microfluidic and MEMS technologies, biochips such as the lab-on-a-chip (LOC) devices are at the brink of revolutionizing the medical disease diagnostics industries. Remarkable advancements in the biochips industry are making products resembling Star Trek.s "tricorder" and handheld medical scanners a reality. Soon, doctors can screen for cancer at the molecular level without costly and cumbersome equipments, and discuss treatment plans based on immediate lab results. This paper develops a roadmap for a hypothetical company (XI) which is seeking to be successful in this market. The roadmapping process starts with gathering data through literature research and expert opinions, and progress through defining the market/product/technology layers, linking and integrating these layers, and finally creating a labon-a-chip for disease diagnostics technology roadmap.